BUDDHIST METHODS OF TEACHING SOCIAL STUDIES IN THE 21st CENTURY - Visudtho (Kotsunton) , Phramaha Aekachai (Journal of Buddhist Education and Research (JBER), 2021)
Buddhism method of teaching, is a method that can be applied in the development of learners according to the era. The Buddha disseminated the dhamma that he had enlightened for the people of all groups to learn. The teaching of the Buddha there are four main characteristics: 1. Santasana, in his teaching and teaching, will explain to the audience clearly, clearly, and actually see it. 2. His body will explain to the audience that what is said That is the truth. 3. Samut Techana: He will use the method to stir up his audience. They are eager to follow that principle successfully and 4. Seminariness in lecturing Dharma He will create an atmosphere conducive to learning. The world society in the 21st century has progressed in science and technology. Learning management is being done in a more interdisciplinary way. And integrate 21st century skills into all core subjects, such as world knowledge, knowledge of finance, economics, business and entrepreneurship, knowledge of good citizenship, health knowledge, environmental knowledge, etc. However, the Buddhist teaching method of the Buddha that had previously laid out the principles of teaching was still applied in order to achieve world-wise teaching and not abandon the Dhamma according to the Buddha’s line. "Knowledge and Morality".